2016
DOI: 10.1038/srep37004
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant SSEA-4 upregulation mediates myofibroblast activity to promote pre-cancerous oral submucous fibrosis

Abstract: Oral submucous fibrosis (OSF), regarded as a precancerous condition, is characterized by juxta-epithelial inflammatory reaction followed by fibro-elastic change in the lamina properia and epithelial atrophy. The pathologic mechanisms of OSF still need to be further clarified. In the study, we investigated the functional expression of SSEA-4, which is a well-known stemness marker, in myofibroblast activity and the clinical significance in OSF tissues. The expression of SSEA-4 in OSF was evaluated by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Myofibroblast can be formed by transdifferentiation of oral keratinocytes activated by arecoline. A study demonstrated that the expression of stage-specific embryonic antigen-4 (SSEA-4, a sialyl-glycolipid) induced by arecoline in buccal mucosal fibroblasts was significantly increased in AN chewing-associated OSF tissues.Knockdown of SSEA-4 synthesis might abolish MFB activity in fibrotic buccal mucosal fibroblasts 21.…”
mentioning
confidence: 99%
“…Myofibroblast can be formed by transdifferentiation of oral keratinocytes activated by arecoline. A study demonstrated that the expression of stage-specific embryonic antigen-4 (SSEA-4, a sialyl-glycolipid) induced by arecoline in buccal mucosal fibroblasts was significantly increased in AN chewing-associated OSF tissues.Knockdown of SSEA-4 synthesis might abolish MFB activity in fibrotic buccal mucosal fibroblasts 21.…”
mentioning
confidence: 99%
“…Thirteen studies included normal oral mucosa for comparison, whereas two studies included fibrous hyperplasia with normal epithelium and one study included hyperkeratosis. Three studies detected myofibroblasts in the stroma of the normal oral mucosa (Angadi, Kale, & Hallikerimath, ; Sarode, Sarode, Deshmukh, Raktade, & Patil, ; Yu, Yu, & Chang, ). Of 189 normal oral mucosa samples, 20 (10.6%) samples were positive for myofibroblasts, 16 showing scarce cells and four with an abundant number of cells.…”
Section: Resultsmentioning
confidence: 99%
“…In OSMF, of 213 cases from six studies, 188 (88.3%) were positive for myofibroblasts. Four studies (Angadi et al., ; Gupta, Metgud, & Gupta, ; Sarode et al., ; Yu et al., ) demonstrated that the presence of myofibroblasts is significantly higher in OSMF compared with normal oral mucosa. A statistical significance was also noted between advanced OSMF (cases with dysplasia) compared to early OSMF (cases without dysplasia), as reported by Angadi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Primary normal buccal mucosa fibroblasts (BMFs) and fibrotic buccal mucosa fibroblasts (fBMFs) were isolated from normal human buccal oral mucosa and OSF lesions, respectively, with written informed consent from patients. These patient-derived fBMFs exhibited myofibroblasts characteristics and have been used in several studies [6,31]. Cells were cultured as previously described [6], and passaged routinely at 90% confluence.…”
Section: Cell Culture For Buccal Mucosa Fibroblasts (Bmfs) and Fibrotmentioning
confidence: 99%